Forty-three years of Ramsar and urban wetlands. (May 2015) - Hettiarachchi, Missaka; Morrison, T.H.; McAlpine, Clive
Highlights: Ramsar convention is the backbone of modern wetland management theory and practice. However urban wetlands management remain under-represented in the Ramsar framework. We empirically interrogate the efficacy of the Ramsar framework in urban wetland governance focusing on two emerging cites. Four conceptual weaknesses of the current Ramsar framework are highlighted. We suggest pragmatic and strategic changes to overcome and mitigate these drawbacks. Abstract: The Ramsar Convention is unquestionably the backbone of modern wetland management theory and practice. In the last four decades, it has mainstreamed wetlands in the environmental discourse and fostered the development of a comprehensive institutional framework for wetland governance. However, many of the wetlands that occur in human-dominated landscapes remain acutely threatened. The problem is most alarming in urban areas, especially in the fast expanding cities of the developing world, where unprecedented wetland destruction is leading to recurring environmental disasters. This triggers the question: are these failures in wetland governance purely induced by factors exogenous to Ramsar-based institutions or are they manifestations of conceptual drawbacks within Ramsar conceptual framework. Here, we investigate the success and failures of the application of the Ramsar framework's policy directives and management guidelines for urban wetlands using two rapidly expanding cities in South Asia as case studies – Colombo (Sri Lanka) and Kolkata (India). We conclude that despite its remarkable achievements over the past four decades, the Ramsar framework has several conceptual drawbacks that weaken its effectiveness in complex urban contexts. An inadequate recognition of the complex dynamics of urban social-ecological systems, an inadequate recognition of the political complexity of the policy processes, and a lack of an environmental justice perspective are the main shortcomings contributing to failures in urban wetlands governance. While we acknowledge that some solutions are contingent upon national and transnational level socio-political processes and reforms, we offer a set of technical and strategic modifications to the Ramsar framework that can significantly improve its effectiveness in urban wetlands governance.